Revisiting the life and thought of Dr.Burhanuddin al-Helmy - Suzy Aziziyana Saili; Khairulnizam Mat Karim (Universiti Kebangsaan Malaysia, 2013)
Burhanuddin al-Helmy is the least known name in Malaysian history. However, his role and thought cannot simply be dismissed although some of it were considered as controversial, and him be labelled as radical Malay leader. But one has to browse through his life and thought in order to determine his nature of being. Dr.Burhanuddin is a man of his time, experiencing the downside of British colonization and Japanese occupation. His personal experience in India and Palestine had shaped his conviction that Malaya and the Malay world need to be independent from the British rule. An active man in politics seen especially in his involvement in PKMM (Parti Kebangsaan Melayu Malaya) and Parti Islam seTanah Melayu (PAS), but what is more important is his three most prevalent ideology. He stressed on Malay nationalism; he envision it as a nationalism for independence,humanity and well being; the idea of Greater Malaya; a unification with Indonesia in which he sees it as a political unification for all Malays in the Malay world, and; the influence of Malay rulers; which he is kind of sceptic towards the Malay sultan whom he viewed as jeopardizing the interests of the people.